Association of Chest X-Rays Features with the Length of Stay in Suspected COVID-19 Status - Zulmansyah Zulmansyah; Gaga Irawan Nugraha; Dwi Agustian; Dida Akhmad Gurnida (Universitas Islam Bandung, 2021)
Coronavirus disease 2019 (COVID-19) is a new type of respiratory infection that first emerged in December 2019 in Wuhan, Hubei, China. COVID-19 is caused by a new variant of virus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Examining the chest x-rays is one technique to diagnose COVID-19. This study aims to determine the association of chest x-rays features in suspected COVID-19 patients with the length of stay at Al-Ihsan Regional General Hospital West Java Province and Banten Regional General Hospital in June–November 2020. The subject was 29 COVID-19 people were confirmed, whereas 31 people were not. The statistical analysis used Pearson correlation and multi-linear regression. This study found that tuberculosis had a strong association with length of stay (p value=0.048, association=0.4), and also there is a robust association between bilateral pneumonia and duration of stay (p value=0.028, association=0.873). A linear regression model discovery of TB chest x-rays on the subject raises the treatment by 0.5867 days. In addition, the discovery of bilateral pneumonia increases the length of stay of treatment by 0.32218 days more than the discovery of unilateral pneumonia. In general, tuberculosis, bacterial pneumonia, viral pneumonia, and bilateral pneumonia together affected the outcome of length of stay of patients with suspected COVID-19. ASOSIASI GAMBARAN RONTGEN TORAKS DENGAN LAMA RAWAT PADA PASIEN SUSPEK COVID-19Coronavirus disease 2019 (COVID-19) adalah jenis infeksi saluran pernapasan baru yang pertama kali mewabah pada Desember 2019 di Wuhan, Hubei, Cina. COVID-19 disebabkan oleh varian virus baru yang disebut severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Pemeriksaan rontgen toraks merupakan salah satu teknik mendiagnosis COVID-19. Penelitian ini bertujuan mengetahui asosiasi gambaran rontgent toraks pada pasien suspek COVID-19 dengan lama rawat inap di RSUD Al-Ihsan Provinsi Jawa Barat dan RSUD Banten pada Juni–November 2020. Subjek penelitian adalah 29 orang terkonfirmasi COVID-19 dan 31 orang tidak. Analisis statistik menggunakan korelasi Pearson dan regresi multilinier. Penelitian ini menemukan bahwa tuberkulosis memiliki hubungan yang kuat dengan lama perawatan (p=0,048; asosiasi=0,4) dan juga terdapat hubungan yang kuat antara pneumonia bilateral dan lama perawatan (p=0,028; asosiasi=0,873). Penemuan model regresi linier rontgent toraks TB pada subjek meningkatkan risiko perawatan 0,5867 hari lebih lama. Selain itu, penemuan pneumonia bilateral meningkatkan risiko perawatan 0,32218 hari lebih lama dibanding dengan penemuan pneumonia unilateral. Secara umum, tuberkulosis, pneumonia bakteri, pneumonia viral, dan pneumonia bilateral secara bersama-sama berpengaruh terhadap luaran lama rawat inap pasien suspek COVID-19.